REGULASI EMOSI ISTRI YANG MEMILIKI SUAMI STROKE - Dewi K, Oktavia (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2012)
AbstractThe presence of stroke experienced by the husband in a family is certainlygoing to affect the lives of all the other family members, especially his wife andchildren.The purpose of doing research is to know the description of emotion aswell as how the regulation of emotion associated with stokes wife husbandand factors that influence the use of emotion regulation as a result of the eventsthat give rise to emotionIn this research using methods qualitative with the approachphenomenology. The technique of collecting data in this research is using methodsobservation and an interview conducted to a subject and significant other. Asubject of study that is, two people wife which a husband has a stroke a.s 58years and 68 years. Emosi-emosi experienced by the wife of which a husbandhas a stroke in this research is quite varied. Angry, emotion sad, love andharapan perceived almost entirely by the subject of associated with comportmentand the condition of the husband. Regulatory processes emotion used by thesubject of another pemilihan situation, between change the situation, the spreadof attention, cognitive change, change response.The result showed wife which a husband has a stroke suffered a greatvariety of emotions between another negative emotions as shocked stress,impatient, angry, cry, sad, stress, aggravation, appear and pressed, a positiveemotion as patience, altruistic, receive, surrender, hopes empathy, glad when itcan be joking with husband, coping and factors that affects the use of emotionstressor, among other regulations physiological factors, a factor of age, cognitive,social aspect, especially the influence of the family cultureConclusion this research is the capacity of varying regulatory emotioneach individual influenced by stressor, physiological factors, a factor of age,cognitive, social aspect, especially the influence of the family and culture.Key words : regulation of emotion, stroke,